Teaching and Learning English by Using Canva: Instructors and Students’ Perceptions at OTC Bali Gianyar - Susanto, I Wayan Erik; Udayanie, Ayu Gde Chrisna (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study explores the perceptions of instructors and vocational students at OTC Bali Gianyar regarding the use of Canva in English language teaching and learning. Using a descriptive qualitative design, data were collected through questionnaires distributed to 4 instructors and 30 students from the Hospitality and Tourism program. The findings reveal that both groups hold positive perceptions of Canva as a learning tool. Instructors reported high levels of usefulness (81.6%), ease of use (85%), and accessibility (85%), while students also expressed favorable views with percentages of 81.9%, 75.9%, and 83.8%, respectively. Canva was recognized as an effective and creative platform that facilitates the creation of engaging learning media, supports online and offline instruction, and offers attractive design features. Beyond improving English learning, Canva fosters creativity, digital literacy, collaboration, and learner autonomy, making it a valuable resource for vocational education in the digital era.